Identification and functional characterization of T-cell exhaustion-associated lncRNA AL031775.1 in osteosarcoma: a novel therapeutic target - Wang, Yameng; Yuan, Jinghong; Guo, Keying; Zhang, Zhuoer; Zhu, Junchao; Arya, Shahrzad; Huang, Guowen; Li, Shengqin; Chen, Qi; Liu, Xijuan; Jia, Jingyu (Frontiers in Immunology, 2025)
BackgroundOsteosarcoma, an aggressive bone malignancy predominantly affecting children and adolescents, presents significant therapeutic challenges with a 5-year survival rate below 30% in metastatic cases. T-cell exhaustion, characterized by the overexpression of immune checkpoint molecules, contributes to osteosarcoma progression and immune evasion. Although targeting these inhibitory pathways has shown potential in restoring T-cell activity, the molecular regulators of T-cell depletion in osteosarcoma are poorly understood.MethodsThis study employed comprehensive bioinformatics analyses on osteosarcoma samples from the TARGET database, combined with normal tissue data from the GTEx database, to identify T-cell exhaustion-associated genes and their co-expressed long non-coding RNAs (lncRNAs). Gene ontology and KEGG pathway analyses were used to elucidate immune-related pathway enrichments. A six-lncRNA prognostic model was established using LASSO regression and validated in separate cohorts. Functional assays evaluated the impact of the lncRNA AL031775.1 on osteosarcoma cell behavior and T-cell function.ResultsTwenty-four key T-cell exhaustion-related genes were identified and significantly enriched in immune-related pathways, indicating their importance in the osteosarcoma immune microenvironment. The constructed six-lncRNA model stratified patients by survival prognosis, showing robust predictive performance across cohorts. Among the six identified lncRNAs, AL031775.1 is notably downregulated in osteosarcoma patients and significantly promotes osteosarcoma cell proliferation, migration, and invasion while contributing to T-cell exhaustion. In T cells, downregulation of AL031775.1 impairs antitumor immunity, upregulates immune checkpoint molecules LAG3, PD1, and CTLA4, and diminishes T-cell cytotoxic activity against tumor cells.ConclusionThis study identifies a novel six-lncRNA prognostic model and highlights the therapeutic potential of AL031775.1 in managing osteosarcoma by enhancing T-cell immunity and counteracting tumor progression. Targeting AL031775.1 represents a promising approach to improve immunotherapy efficacy in osteosarcoma. These findings provide critical insights into the molecular regulation of T-cell exhaustion and suggest a new avenue for therapeutic intervention.